2022
DOI: 10.1021/acsbiomaterials.1c01247
|View full text |Cite
|
Sign up to set email alerts
|

Potential Load-Bearing Bone Substitution Material: Carbon-Fiber-Reinforced Magnesium-Doped Hydroxyapatite Composites with Excellent Mechanical Performance and Tailored Biological Properties

Abstract: A potential load-bearing bone substitution and repair material, that is, carbon fiber (CF)-reinforced magnesium-doped hydroxyapatite (CF/Mg-HAs) composites with excellent mechanical performance and tailored biological properties, was constructed via the hydrothermal method and spark plasma sintering. A high-resolution transmission electron microscopy (TEM) was employed to characterize the nanostructure of magnesium-doped hydroxyapatite (Mg-HA). TEM images showed that the doping of Mg-induced distortions and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In addition, weak peaks ascribed to CO characteristic of CO 3 2– appear at 865, 1437, and 1452 cm –1 , forming a small amount of carbonate-substituted apatite . This phenomenon is caused by the adsorption of carbon dioxide in the atmosphere by highly active hydroxyapatite crystals with polar groups removed by boiling holding treatment with kerosene, resulting in a small almount of carbonate apatite, which has excellent biological activity and biocompatibility . These also prove the application prospect of this material in carbon capture.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, weak peaks ascribed to CO characteristic of CO 3 2– appear at 865, 1437, and 1452 cm –1 , forming a small amount of carbonate-substituted apatite . This phenomenon is caused by the adsorption of carbon dioxide in the atmosphere by highly active hydroxyapatite crystals with polar groups removed by boiling holding treatment with kerosene, resulting in a small almount of carbonate apatite, which has excellent biological activity and biocompatibility . These also prove the application prospect of this material in carbon capture.…”
Section: Resultsmentioning
confidence: 82%
“…The nHA prepared by Zhao et al 118 by the hydrothermal method is hexagonal, and the average length and width of the particles are about 100 and 30 nm, respectively. The average length and width of Mg-nHA prepared in the same way are about 80 and 30 nm.…”
Section: Synthesis Methods Of Magnesium-doped Nanohydroxyapatitementioning
confidence: 99%
“…The aspect ratio of the nanoparticles was found to decrease with increasing Mg content, which is thought to be caused by the suppression of grain growth and lattice distortion when the Mg element is substituted in nHA. 118 In the hydrothermal synthesis of Mg-nHA composite with an acid–base slow-release agent at pH = 3 and a temperature of 180 °C, Zhang et al 119 found that with the increase of Mg 2+ content. This is mainly because the radius of Mg 2+ (70 pm) is smaller than that of Ca 2+ (100 pm).…”
Section: Synthesis Methods Of Magnesium-doped Nanohydroxyapatitementioning
confidence: 99%
“…The main limitation of these carbon nanomaterials is their size, which is generally less than 200 nm, with the risk of being eliminated by the human immune system or the target organ [18][19][20]. We and others have shown that ACs, under the form of carbon fibers, are interesting materials for bone reconstruction [21][22][23][24][25][26]. In pilot studies performed in a rat model of large bone cortical defects, we have shown that activated carbon fiber cloth is highly biocompatible and fully osteointegrated after 6 months post-surgery [27].…”
Section: Introductionmentioning
confidence: 99%